Surveillance of Influenza in Outpatient ILI Cases in Community Based Medical College Hospital, Bangladesh (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13862 Community Based Medical Journal Vol.1(2) 2012 38-47